Protecting Minds - Douglas, Thomas (Oxford University Press, 2026)
It is widely accepted that we each possess a right against interference with our body. In this book, Thomas Douglas argues that we each also possess an analogous right against interference with our mind. Douglas offers two arguments in favour of the view that we possess this right. The first appeals to intuitions regarding cases. Douglas describes a series of cases in which one individual influences the mind of another in a seemingly wrongful way, and argues that we can best account for the wrongfulness of these influences by invoking a right against mental interference. The second argument appeals to the notion of self-ownership. According to this argument, our ownership of ourselves implies ownership of our minds, which in turn implies a right against interference with our minds. Douglas then turns to the task of defining the scope of the right against mental interference. On the view he develops, the right against mental interference protects us against some actions that alter our mental states via processes that are insensitive to the reasons that bear on the alteration. The interventions that most obviously infringe the right are ‘nonconsensual neurointerventions’—interventions that alter a person’s mental states by physically modulating their brain states—and are performed without the target’s consent. But Douglas argues that some psychological forms of influence can infringe the right too. Examples include the use of subliminal imagery and conditioning-based interventions, such as the use of loot boxes in computer games.